Immigrant Integration and COVID-19 - Rebhun, Uzi (Border Crossing, 2021)
Covid-19 has thrust millions of people who have recently crossed international borders into unprecedented social and economic havoc. The patterns of immigration and settlement in a new country, on the one hand, and the nature of the virus, on the other hand, have placed immigrants at high risk of infection, possibly generating or accelerating anti-immigration sentiments among the local population. In this viewpoint, I discuss five complementary aspects of the migration-pandemic nexus: immigrants’ legal status, language proficiency, ethnic segregation, religiosity, and economic wellbeing. My concluding remarks carry several implications for policy.